Industrialization — one of the key directions of Kazakhstan's development in the new economic reality - Karenov, R.S. (BUKETOV BUSINESS REVIEW, 2017)
Provided the value of industrialization, in fact became one of the few development tools that allows businesses and investors to create new projects. The specificity of industrial-innovative potential of Kazakhstan, as well as the conditions conducive to the transition to sustainable development of the republic's economy. It is stated that in the industrial development of Kazakhstan can not be limited achieved, it is necessary to expand and upgrade measures to promote knowledge-based economy model. Attention is drawn to the fact that each energy source has advantages and disadvantages, so that during the development of industrialization and consumption of these sources in the world and Kazakhstani Energy substantially different. It is concluded that under the conditions of industrialization, energy technologies, based on renewable energy, fossil and nuclear fuels, the use of nuclear fusion of hydrogen energy should not be viewed as competing but as a complement each other to create energy security in the Republic of Kazakhstan. The feasibility of creating a common energy market within the EAEC. It is noted that the largest energy EAEC members – Russia and Kazakhstan – is the core economies, which affects all sectors of activity, and it has strengthened the integration cooperation within the Union.